2016
DOI: 10.1186/s12889-016-3023-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and understanding sedentary behaviour in office-based working adults: a mixed-method approach

Abstract: BackgroundSedentary behaviours (SB) can be characterized by low energy expenditure in a reclining position (e.g., sitting) often associated with work and transport. Prolonged SB is associated with increased risk for chronic conditions, and due to technological advances, the working population is in office settings with high occupational exposure to SB. This study aims to assess SB among office workers, as well as barriers and strategies towards reducing SB in the work setting.MethodsUsing a mixed-methods appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 40 publications
(57 reference statements)
6
76
2
5
Order By: Relevance
“…This suggestion is strengthened by two Singaporean studies that reported significantly more accelerometer-measured SB during work-versus non-work days in working adults. 24,90 Considering the strong cultural emphasis on work-related success leading to long working hours in many Asian countries, 100 and the increasing number of people with tertiary education that often leads to (sedentary) desk-bound jobs, the office is an important setting for SB interventions. That such interventions…”
Section: Correlates Of Sb In Asian Adultsmentioning
confidence: 99%
“…This suggestion is strengthened by two Singaporean studies that reported significantly more accelerometer-measured SB during work-versus non-work days in working adults. 24,90 Considering the strong cultural emphasis on work-related success leading to long working hours in many Asian countries, 100 and the increasing number of people with tertiary education that often leads to (sedentary) desk-bound jobs, the office is an important setting for SB interventions. That such interventions…”
Section: Correlates Of Sb In Asian Adultsmentioning
confidence: 99%
“…These reported sitting times are consistent with previous self-reported (Kazi et al, 2014) and objectively measured studies (Thorp et al, 2012;Waters et al, 2016). This further supports the evidence that SB is highly prevalent within desk-based occupations.…”
Section: Self-reported Sitting Timessupporting
confidence: 89%
“…Previous research has reported small sample sizes (Waters et al, 2016) The social ecological model of SB (Owen et al, 2011) has been used to underpin workplace SB interventions (Healy et al, 2016;Mackenzie et al, 2015) as discussed in the Literature Review (Chapter 2). The findings of Study 1 support this, as individual, social, organisational, and environmental factors were found to influence SB.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lead to a sedentary behaviours (SB) which lead to low energy expenditure in a reclining position. If this condition prolonged, it can lead to severe injuries caused by static posture, forceful exertion or repetitive movement [2]. Ultimately, this will caused discomfort or unpleasant condition to human body of workers.…”
Section: Introductionmentioning
confidence: 99%